Big data analytics strategy formulation: a case study of big data analytics organizations in South Africa - Kondo, Never (Department of Information Systems, 2025)
Storing data as big data in isolation lacks inherent value until it undergoes analysis to yield valuable insights. The main goal for organizations investing in big data analytics (BDA) for digital transformation is to enhance decision-making and generate organizational value. However, most organizations struggle to improve performance or gain a competitive advantage from BDA insights. This is primarily due to a failure to formulate and articulate BDA strategies to digitally transform business outcomes by making better insightful business decisions. As a result, top management continues to grapple with pervasive BDA issues that they find difficult to comprehend. This research explores the foundational underpinning components that inform the formulation of a BDA strategy for organizations in South Africa. The importance of the South African context is that South Africa is classified as a leading emerging economy in Africa, with the potential to bridge the digital divide between developed and developing countries on the global market. Introducing BDA technologies can benefit South African organizations across multiple industries by enabling equitable digital economy participation in order to compete with global organizations and develop much needed future data analytics skills on the African continent. The research followed a general inductive approach, through a multiple case study of two prominent BDA organizations in South Africa. The research was conducted as a cross- sectional study and followed an inductive approach to formulate theory based on gathered evidence. In addition, a priori framework guided research concepts and principles to be explored through the inductive experience. The empirical findings unveiled twelve key themes that inform the formulation of a BDA strategy in South African organizations, categorized into internal and external organizational components. Internally: Organizations require well-articulated BDA business goals and objectives that are aligned with the required, BDA techniques to be utilised and executed, by the competent people possessing essential skills to manage BDA complexities brought about by the various big data characteristics. The organizations have to utilize, technologically advanced tools from suppliers to further enhance, their competitive advantage in the market they operate, as outlined by the determinants of Porter's 5 Forces model, in a cost-efficient manner. Simultaneously, organizations must consider external components such as, the legal and regulatory climate, social trends, economic factors, customer behaviour and competition outlook. The amalgamation of the BDA strategy components is crucial for delivering valuable business outcomes that surpass BDA investment costs. The research contributes to the field of Information Systems by providing a novel model that enriches extant literature and helps South African organizations with guidelines to follow when formulating a BDA strategy, by identifying and outlining the key foundational components that should inform a BDA strategy.